Design Thinking Research Making Distinctions: Collaboration versus Cooperation (Understanding Innovation,, 2018)
More and more organizations have experienced the impact of design thinking on their innovation culture. People can see the way it changes how they and their coworkers innovate, how it affects their teamwork, and the impact it has on the quality of their output. The desire to understand the reason for this impact and to improve our knowledge about innovation is what drives the HPI Stanford Design Thinking Research Program. Since 2008 scientists from the Hasso Plattner Institute and Stanford University have engaged in multifaceted research projects to learn more about the underlying principles of this method and how and why it works. The outcomes of their studies, experiments and investigations in this eighth year of the program have been compiled in this book. This volume presents a broad range of findings on team interaction, and highlights research into the tools and techniques that foster productive collaboration. Moreover, it addresses design thinking education and training, presenting promising new approaches and tools. The final part of this publication compiles findings on how design thinking is applied in practice. The results of this rigorous academic research are not intended to be discussed exclusively in the scientific community. The findings, as well as the new design thinking approaches and tools, are available to anyone seeking to support drive innovation through collaboration, be it in companies or in society.